Genômica de um baculovírus isolado da lagarta praga de leguminosas Urbanus proteus (Linnaeus, 1758) (Lepidoptera: Hesperiidae) - Santos, Ethiane Rozo dos (2018)
Baculoviruses are insect viruses largely used as vectors for gene expression and biopesticides. These viruses can efficiently infect larvae of several agricultural pests worldwide, causing a lethal disease. In this work, a novel baculovirus isolated from the larval stage of Urbanus proteus (L.), the bean leafhopper caterpillar was found in the 1980s and the complete genome was characterized. This was an important pest of several legumes in Brazil and belongs to the butterfly family Hesperiidae, from where no baculovirus genome sequence has been described. This new virus was shown to have the smallest genome among all alphabaculoviruses sequenced to date, with 105,555 bp and 119 putative ORFs. Ten unique genes, seven bro genes and the 38 baculovirus core genes were found. UrprNPV was found to be related to the Adoxophyes-infecting baculoviruses AdorNPV and AdhoNPV, with high genetic distance and long branch length. Interestingly, few individual core gene-based phylogenies were found to support the relationship of UrprNPV to both AdorNPV and AdhoNPV. Importantly to note that the increase in the number of completely sequenced baculoviruses points to an interesting way of understanding baculoviruses and their evolution, potentially helping the use of baculovirus, both as biopesticide and expression vectors.